Anti-bacterial and multi-functional smart wearable sensor based on organo-hydrogel for diagnosis of the anterior cruciate ligament injuries, and sensing glove for rehabilitation of joints motion. (August 2022) - Elksass, Samar; Alkabes, Hend A.; El-Kemary, Nesma M.; El-Kelany, Khaled E.; El-Kemary, Maged
Abstract: Stretchable multi-functional electronic skin devices capable of interface with parts of human body and/or internal organs to diagnose the anterior cruciate ligament (ACL) injuries and rehabilitation of human joint motion are attractive candidates for next-generation wearables biomedical devices, soft robots, and the Internet of Things (IoT). Such devices need to be of excellent mechanical property, anti-freezing, antibacterial, biocompatible to be comfortable to wear for long term usage and accommodate strains from repeated movement and prevent skin irritation. To address this need, we introduced conductive organo-hydrogels based on silver quantum dots (COH@AgQDs) as multi-functional stretchable sensor with outstanding high-performance diagnostic capabilities. We demonstrated a prototype from the developed sensors integrated into a wirelessly Arduino board and a smartphone was selected to transmit data which offers promising wireless system for rehabilitation after surgeries. Additionally, the developed device has ability to differentiate between ACL injury and healthy knee with different pattern shapes and high sensitivity. Moreover, the flexible sensor can inhibit the growth of bacteria (Escherichia coli (E-coli)) and Staphylococcus aureus (S. aureus) and protect human health for long-term use. It exhibited outstanding anti-freezing property (−53 °C), antibacterial, self-healing, robust mechanical property (strain 420% at stress 96 kPa), and high linearity. Graphical Abstract: ga1 Highlights: We synthesized 3D nanocomposites organo-hydrogel as stretchable multi-functional electronic skin strain sensor. Ag nanowires decomposed into Ag QDs in the presence of PDA-TiO2 nanocomposite without external irradiation or heating. The developed device has employed for Rehabilitation of Joints Motion using wireless Sensing Glove. The developed device has ability to differentiate between ACL injury and healthy knee. The flexible sensor can inhibit the growth of bacteria and protect human health for long-term use.